54.2k views
5 votes
25. Simplify the following expression.


Question 25 please

25. Simplify the following expression. Question 25 please-example-1
User Johan Gov
by
6.2k points

2 Answers

2 votes

Answer:

3 -√5

Explanation:

(√5 + 1) / (2 + √5)

Multiply top and bottom of the fraction by the conjugate of 2 + √5 which is 2 - √5.

By doing this we rationalise the denominator:

= (√5 + 1 ) * ( 2 - √5) / (2 + √5)(2 - √5)

= (√5 + 1 ) * ( 2 - √5)/ (4 - 2√5 + 2√5 - 5)

= (2√5 - 5 + 2 - √5) / (4 - 5)

= (√5 - 3) / -1

= 3 -√5

User Bassam Qarib
by
5.3k points
5 votes

I hope this helps you

25. Simplify the following expression. Question 25 please-example-1
User George Koller
by
5.4k points